1963
DOI: 10.1126/science.140.3569.898
|View full text |Cite
|
Sign up to set email alerts
|

Erosion and Deposition of Italian Stream Valleys During Historic Time

Abstract: The recent geologic history of small streams in east-central Sicily and southern Etruria has been dated archeologically. In Sicily a period of deposition began post 8th century B.C. and had ended by 325 B.C. After a period of erosion, another, less extensive, alluviation took place, probably in medieval time. North of Rome in southern Etruria an alluviation that began no earlier than the late Roman empire probably continued into medieval time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 1 publication
2
21
0
2
Order By: Relevance
“…Given that this sequence of events accurately summarizes the evolution of the modern floodplain, it is suggested that in the case of the Lower Vasilikos Valley both the channel zone and floodplain deposits should be regarded as components of the sequence of alluviation which Vita-Finzi (1969) associates with the formation of the Younger Fill. The clear evidence of a phase of (channel zone) alluviation in the Lower Vasilikos Valley which precedes the deposition of the 'Younger Fill' proper (as it is described by Vita-Finzi, 1969) is paralleled by evidence from Sicily (Judson, 1963), Greece (Paepe, 1969) and Spain (van Zuidam, 1975). The sequence of alluviation which is associated with the construction of the modern floodplain is generally in agreement with Flemming's (1978) and Flemming et al's (1978) hypothesis of the subsidence of the south coast of Cyprus over the past 4000 years, and the regional eustatic rise in sea level that has occurred during the past 7000 years.…”
Section: Termed the 'Oldermentioning
confidence: 82%
“…Given that this sequence of events accurately summarizes the evolution of the modern floodplain, it is suggested that in the case of the Lower Vasilikos Valley both the channel zone and floodplain deposits should be regarded as components of the sequence of alluviation which Vita-Finzi (1969) associates with the formation of the Younger Fill. The clear evidence of a phase of (channel zone) alluviation in the Lower Vasilikos Valley which precedes the deposition of the 'Younger Fill' proper (as it is described by Vita-Finzi, 1969) is paralleled by evidence from Sicily (Judson, 1963), Greece (Paepe, 1969) and Spain (van Zuidam, 1975). The sequence of alluviation which is associated with the construction of the modern floodplain is generally in agreement with Flemming's (1978) and Flemming et al's (1978) hypothesis of the subsidence of the south coast of Cyprus over the past 4000 years, and the regional eustatic rise in sea level that has occurred during the past 7000 years.…”
Section: Termed the 'Oldermentioning
confidence: 82%
“…They were easily identified through the dark color of the topsoil, because rather than distinct layers the volcanic material often appeared as abundant fine angular pyroclastic particles. Therefore, the presence in the topsoil of pyroclastic material was a proxy in aid of the evaluation whether a soil has been recently truncated or "aggraded" after the last eruptions (for a discussion on ash fall as an excellent temporal marker for studying gradational processes in the Mediterranean; see Brown, ; Judson, ; Lefèfre, Raynal, Vernet, Kieffer, & Piperno, ; Vita‐Finzi & Judson, , pp. 239–242).…”
Section: Evaluating Geomorphological Biasesmentioning
confidence: 99%
“…It is also the first site at which the archaeological content has been intensively investigated. Other studies have shown that this period of stream alluviation was widespread through the Mediterranean basin (Judson 1963a and1963b;Vita-Finzi 1969). One is at the stream-side site along the Torrente Valchetta near Veii (Ward-Perkins and Judson, unpublished) and the second on the River Treia at Narce (Cherkauer 1976).…”
Section: Alluviation At the Site O/fosso Della Crescenzamentioning
confidence: 85%
“…On the basis of cartographic evidence I have suggested that it was prior to A.D. 1534 (Judson 1963a). On the basis of cartographic evidence I have suggested that it was prior to A.D. 1534 (Judson 1963a).…”
Section: Cause Of Alluviationmentioning
confidence: 99%